Strategies for Reducing Heuristic Bias in Investment Decision Making: A Study of Individual Investors - Putria, Marissa; Wardoyo, Cipto; Tien Irafahmi, Diana (International Journal of Science, Technology & Management, 2025)
This study focuses on what strategies are used to reduce the negative impact of using heuristics in decision making. This study aims to examine in depth the relevant strategies that can be used to reduce heuristic bias in investment decision making, especially among individual investors. Qualitative research method with a case study approach, research data was collected using purposive sampling technique on individual investors who actively invest in the capital market, either through stocks or digital platforms such as online mutual funds and trading applications. The research findings consist of one main theme that is in accordance with the focus of the research, namely strategies to overcome heuristic bias, which includes four sub-themes consisting of systematic evaluation and planning, application of practical strategies and self-discipline, use of guidelines for consistency and objectivity, and training to increase awareness and self-control. The findings contribute to the literature in behavioral finance and financial psychology, especially by expanding the understanding of the self-control mechanisms used by investors in responding to cognitive biases. These findings also support and strengthen prospect theory by adding dimensions of contextual and individual control strategies in responding to investment risk and uncertainty.